Penatalaksanaan Fisioterapi Padabell's Palsy Dextra Di Rumah Sakit Al Dr.Ramelan Surabaya - Sholihah, Mar'atush, Yulisna Mutia Sari, SSt.FT.,MSc (GRS) (2016)
Background : Bell's palsy is a kind of paralysis of acute peripheral nerve VII, and the cause is unknown (idiopathic). In this case, it can be managed with physiotherapy modalities that can reduce pain and increase functional ability of facial muscles by using the modalities of infra red, electrical stimulation, and mirror exercise. Objective: To investigate the implementation of physiotherapy in reducing pain, improving functional ability, and the strength of the facial muscles on the condition of Bell's Palsy using infrared modalities, electrical stimulation, and mirror exercise Results: After doing therapy for six 6 times, it was obtained the result in pain assessment in painfully T0: 5,1, to T6: 1,5, tenderness T0: 7,1, to T6: 2.1, an increase of facial muscle strength M.corrugators superciliiT0: 1, to T6: 3, M.frontalisT0: 1, to T6: 3, M.nasalisT0: 1 to, T6: 3, M.depresor T0: 1, to T6: 3, M.mentalisT0: 1, to T6: 3, M.platysma T0: 1, to T6: 3, there is functional improvement of facial muscles T0: 42, to T6: 46. Conclusion: It is concluded that the application modalities of physiotherapy in the form of Infra Red, Electrical Stimulation, and Mirror Exercise are able to reduce pain, increasing the muscle strength and functional activity of the facial muscles.